The Regulation of Public Company Auditing: Evidence from the Transition to AS5 - DOOGAR, RAJIB; SIVADASAN, PADMAKUMAR; SOLOMON, IRA (Journal of Accounting Research, 2010)
ABSTRACT The replacement of Auditing Standard No. 2 (AS2) by Auditing Standard No. 5 (AS5) creates a natural experiment that sheds light on (1) potential inefficiencies caused by regulatory responses to a political crisis and (2) audit efficiency and effectiveness improvements resulting from the risk‐based approach embodied in AS5. We study these effects by examining the impact of AS5 on audit fees. We find that AS5 audit fees are aligned with auditee fraud risk, but not AS2 audit fees. Second, relative to AS2 benchmark levels, AS5 audit fees are, on average, lower for all auditees. Third, relative to AS2 benchmarks, AS5 fees are lower for lower‐fraud‐risk auditees but greater for higher‐fraud‐risk auditees. Overall, the evidence is consistent with (1) initial overregulation (via AS2) followed by reform (via AS5) and (2) auditors deploying a risk‐based audit approach to obtain both efficiency and potential effectiveness gains in audit production.